Produção e caracterização de hidromel utilizando diferentes cepas de leveduras Saccharomyces - Mileski, João Paulo Fernando (2016)
Beekeeping is an important economic activity in the Southwest of Paraná and the development of honey-based products can be an important alternative to the flow of production and at the same time an interesting way to add value to the product. The mead is a fermented beverage obtained by dilution of the honey in water with addition of nutrients and yeast. In some parts of Europe is a drink very consumed and appreciated in Brazil, however, it is little known and exploited. This study aims to investigate the process of alcoholic fermentation of honey with different strains of Saccharomyces yeast, produce and evaluate fresh and matured mead. The honey for the development of the study was acquired in the Beekeepers Association of the City and subjected to physical and chemical characterization and adulteration, the results showed that the raw material had quality standard and characteristic identity of pure honey bees (Apis mellifera). Knowing the quality of raw material, three different types of yeast (Red Star champagne, Lalvin EC and 1118 Fleischmann) were used for production of mead. The final product was characterized by physical-chemical analysis, volatile compounds were identified and quantified by chromatography. Sensory analysis was performed to identify the greater acceptance of sample, which was subsequently submitted to maturation in oak barrels and balsam. Among the strains used, the yeast Red Star Champagne showed higher ability to convert sugar into alcohol (ethanol), producing a beverage with higher alcohol content. The Lalvin EC 1118 yeast produced a more balanced drink on the alcohol content and residual reducing sugars, while Fleischmann yeast showed less sugar conversion capacity in alcohol, providing drinking less alcohol. The profile of volatile compounds presented in a similar fashion in the three mead formulations developed with different strains of Saccharomyces yeasts, however, the beverage produced from Fleischmann strain showed generally higher amounts of esters linked to fruity aroma and floral. Sensory analysis indicated the drink produced by Fleischmann yeast as the preferred, which was aged in oak barrels and balsam, the maturation stage had a total of 180 days. Among the wood used for the maturation, oak showed greater ability to alter the physical and chemical characteristics of the drink, the color parameter has also been changed more intensely by maturation inoak, which does not indicate that the balsam can not be considered a good alternative to mead maturation.